The appropriation of “nouchi” by the Ivorian French in youth language: a phenomenon of sociolinguistic variation - Yao, Koffi (2020)
The appropriation of the “nouchi” by the Ivorian French is a phenomenon of adoption or the transfer of some expressive neologies and other particular loan words to the juvenile language. In relation to this process, our study raises the problem of the emergence of local French based on these lexical elements methodically selected by listening to musi- cal materials,“zouglou”, “coupé-décalé” and rap, in order to check both the influence of these musical genres, and the processes of (trans)formation of this particular variety of the French language.